The legal framework for energy provisions in the European Union – With special regard to providing of energy provisions within the scope of Article 194(2) TFEU - Backlund, Tove (fi=Turun yliopisto|en=University of Turku|, 2016)
The thesis interprets the caveat of Article 194(2) TFEU in order to assess the use of the Article as a legal basis for energy provisions provided by the European Union. The research subject is the Energy Title in the Treaty of the Functioning of the European Union and the possibilities of the application of the legal basis provided therein. The purpose is analysis of the possibilities for providing of provisions within the scope of the caveat found in Article 194(2) TFEU with special regard to the possibilities of providing renewable energy legislation. The purpose of the thesis is on one hand to provide an overview of the premises for providing of energy provisions in the EU, and on the other hand to analyse the Treaty text in order to determine the legal basis for energy provisions. The ultimate objective is to determine the correct legal basis for renewable energy provisions, aimed at the mitigation of climate change. According to Article 194(2) TFEU, the practice of the shared legislative powers in the field of energy are restricted by the retention of certain energy matters within the power of the Member States. The wording of the caveat containing the restrictions is open to interpretation and has been a subject of extensive discussion. Many scholars have argued that the caveat in Article 194(2) TFEU might obstruct decision-making in energy matters. This argument is contested, and the factual impact of the codification of the energy competences is analysed. The correct legal basis for energy provisions depends on the final interpretation of the text of the caveat and the level of significance of the effect of the measure. The use of Article 194(2) TFEU as a legal basis might not be the only option. There is a possibility that the legal bases within the Environmental Title might be used as legal bases for energy provisions in addition to Article 194(2) TFEU.